DESKRIPSI KESULITAN MAHASISWA PRODI PMA MEMBUKTIKAN TEOREMA STRUKTUR ALJABAR - Suzana, Yenni (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2013)
Prove or evidence is a range of logical argument which explains the truth of statement.Â  Previous justification towards argument means logic. Mathematic says that Theorem is a formal one for inference and axiom of deductive system. Accordingly, mathematic students feel difficult to prove theorem due to their less understanding of definition, use of mathematic terms, and a start to prove.Here, the writer discusses the issue of multivariate statistic technique application for gaining causes of studentsâ€™ difficulties to prove theorem, and it is in structure algebra subject.